2021
DOI: 10.1002/anie.202110545
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Switching of Calmodulin in a Mycobacterium smegmatis porin A (MspA) Nanopore‐Trap

Abstract: Recent developments concerning large protein nanopores suggest a new approach to structure profiling of native folded proteins. In this work, the large vestibule of Mycobacterium smegmatis porin A (MspA) and calmodulin (CaM), a Ca2+‐binding protein, were used in the direct observation of the protein structure. Three conformers, including the Ca2+‐free, Ca2+‐bound, and target peptide‐bound states of CaM, were unambiguously distinguished. A disease related mutant, CaM D129G was also discriminated by MspA, reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…By generating large event amplitudes and rich event features during saccharide sensing, MspA demonstrates a superior performance of saccharide identification in single molecule [20, 25] . According to experimental [29a, 36c, 37] and theoretical assessments, [38] the conical lumen geometry of MspA contributes most to this superior resolution. Discrimination between saccharide isomers or epimers was also demonstrated, further confirming that MspA is structurally superior in saccharide identification.…”
Section: Discussionmentioning
confidence: 99%
“…By generating large event amplitudes and rich event features during saccharide sensing, MspA demonstrates a superior performance of saccharide identification in single molecule [20, 25] . According to experimental [29a, 36c, 37] and theoretical assessments, [38] the conical lumen geometry of MspA contributes most to this superior resolution. Discrimination between saccharide isomers or epimers was also demonstrated, further confirming that MspA is structurally superior in saccharide identification.…”
Section: Discussionmentioning
confidence: 99%
“…Nanopore, an emerging single-molecule sensor which provides rapid and sensitive profiling of nucleotides, , amino acids, biothiols, , neurotransmitter, nucleic acids, , peptides, , and proteins, has a great potential to achieve this task. By introducing chemical reactivity into the nanopore lumen, its sensitivity and selectivity could be further improved, disclosing information that is not easily accessed by other means. ,, Phenylboronic acid (PBA), which is known to form covalent bonds with 1,2 or 1,3-diols in aqueous solution, can bind with polyols including sugars and sugar alcohols. , Recent reports have shown that PBA can serve as a chemically specific adapter of a heterogeneous α-hemolysin (α-HL) permitting the detection of saccharides.…”
Section: Introductionmentioning
confidence: 99%
“…Biological nanopores are a group of transmembrane porin-based sensors originally developed for sequencing of single molecules. Their high sensing resolution also enables direct probing of metal ions, small molecules, nucleic acids, peptides, and proteins at the level of a single molecule. With their chiral lumen environment and a sufficient resolution of sensing, biological nanopores can, in principle, discriminate between enantiomers when the target molecule is transiently trapped near the pore constriction.…”
Section: Introductionmentioning
confidence: 99%